2017
DOI: 10.3855/jidc.8614
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistant Klebsiella pneumoniae isolates from a university hospital in Brazil

Abstract: Introduction: The emergence of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-Kpn) isolates is attracting significant attention in nosocomial infection settings. K. pneumoniae is the main pathogen that harbours blaKPC genes. Methodology: This study evaluated 54 K. pneumoniae carbapenem-resistant isolates from patients hospitalized at the University Hospital of Londrina, between July 2009 and July 2010. The isolates were phenotypically screened for carbapenemase production and submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The MIC 50 and MIC 90 showed several bacterial strains that were highly resistant to the different groups of drugs. The lowest resistance rates were observed against colistin and tigecycline, agreeing with a prior study from Brazil ( Vivan et al, 2017 ). However, emerging colistin resistance has been reported from China ( Liu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…The MIC 50 and MIC 90 showed several bacterial strains that were highly resistant to the different groups of drugs. The lowest resistance rates were observed against colistin and tigecycline, agreeing with a prior study from Brazil ( Vivan et al, 2017 ). However, emerging colistin resistance has been reported from China ( Liu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is implicated in various infections like pneumonia, blood stream infection, urinary tract infection and hepatic abscess. 33 In the current study majority of K. pneumoniae were isolated from urine cultures (29.7%) ( 36 who reported maximum isolation of K. Pneumoniae from urine samples. K. pneumoniae is the second most common cause of UTI after E. coli.…”
Section: )mentioning
confidence: 49%
“…In their study, among the carbapenemases coexpression of bla NDM and bla OXA48 -like was observed in 28%, bla NDM in 19%, bla OXA48 -like in 13% and bla KPC was not found. In the study of Vivan et al, 32 the isolates that were phenotypically screened for carbapenemase production were subjected for genotypic confirmation by PCR (PCR) for KPC, metallo-b-lactamases, OXA-48, and extendedspectrum beta-lactamase genes. PCR analysis demonstrated that all isolates carried bla KPC genes and sequencing showed that all strains belonged to KPC-2 subtype.…”
Section: Discussionmentioning
confidence: 99%